2021
DOI: 10.3390/ijms222011250
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplastic Syndromes and Metabolism

Abstract: Myelodysplastic syndromes (MDS) are acquired clonal stem cell disorders exhibiting ineffective hematopoiesis, dysplastic cell morphology in the bone marrow, and peripheral cytopenia at early stages; while advanced stages carry a high risk for transformation into acute myeloid leukemia (AML). Genetic alterations are integral to the pathogenesis of MDS. However, it remains unclear how these genetic changes in hematopoietic stem and progenitor cells (HSPCs) occur, and how they confer an expansion advantage to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 123 publications
(139 reference statements)
0
9
0
Order By: Relevance
“…6 In MDS, a deficiency of mitochondrial subunits or enzymes has been described. 1 Consistently, an increase in extramitochondrial glucose catabolism despite adequate oxygen availability (aerobic glycolysis), namely the Warburg effect, has been observed. This results in the hypoxia-independent activation of hypoxia-inducible factor 1α (HIF1α) through different intermediate metabolites of the tricarboxylic acid cycle, such as the oncometabolite 2-hydroxyglutarate.…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…6 In MDS, a deficiency of mitochondrial subunits or enzymes has been described. 1 Consistently, an increase in extramitochondrial glucose catabolism despite adequate oxygen availability (aerobic glycolysis), namely the Warburg effect, has been observed. This results in the hypoxia-independent activation of hypoxia-inducible factor 1α (HIF1α) through different intermediate metabolites of the tricarboxylic acid cycle, such as the oncometabolite 2-hydroxyglutarate.…”
mentioning
confidence: 80%
“…by increased erythron iron turnover along with impaired red blood cell (RBC) utilization, but also by a disrupted metabolism. [1][2][3] Glycolysis is the prominent metabolic cascade in RBCs and is currently targeted with pyruvate kinase (PK) activators in clinical trials in rare anemias. AG-946 is an investigational, small-molecule, potent allosteric activator of PK with the potential to enhance RBC functionality and survival by stimulating glycolysis and to improve differentiation of erythroid cells in bone marrow.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Also, MDS cells metabolism can be involved in ROS generation. Healthy HSC use glycolysis for energy production while MDS stem and progenitor cells generate energy via oxidative phosphorylation; as a consequence, ROS levels increases [ 33 ]. In the last years, the role of inflammation was investigated in MDS pathogenesis: many studies showed an increase in pro inflammatory cytokines as IL-1β, IL-6, TNFα, and IFN-γ in low risk MDS [ 34 ].…”
Section: Discussionmentioning
confidence: 99%